Low Lipoprotein(a) Levels Predict Hepatic Fibrosis in Patients With Nonalcoholic Fatty Liver Disease. Issue 3 (22nd October 2021) - Meroni, Marica; Longo, Miriam; Lombardi, Rosa; Paolini, Erika; Macchi, Chiara; Corsini, Alberto; Sirtori, Cesare R.; Fracanzani, Anna Ludovica; Ruscica, Massimiliano; Dongiovanni, Paola
Abstract : Dyslipidemia and cardiovascular complications are comorbidities of nonalcoholic fatty liver disease (NAFLD), which ranges from simple steatosis to nonalcoholic steatohepatitis, fibrosis, and cirrhosis up to hepatocellular carcinoma. Lipoprotein(a) (Lp(a)) has been associated with cardiovascular risk and metabolic abnormalities, but its impact on the severity of liver damage in patients with NAFLD remains to be clarified. Circulating Lp(a) levels were assessed in 600 patients with biopsy‐proven NAFLD. The association of Lp(a) with liver damage was explored by categorizing serum Lp(a) into quartiles. The receiver operating characteristic curve was used to analyze the accuracy of serum Lp(a) in hepatic fibrosis prediction. Hepatic expression of lipoprotein A ( LPA ) and of genes involved in lipid metabolism and fibrogenic processes were evaluated by RNA sequencing in a subset of patients with NAFLD for whom Lp(a) dosage was available (n = 183). In patients with NAFLD, elevated Lp(a) levels were modestly associated with circulating lipids, carotid plaques, and hypertension ( P < 0.05). Conversely, patients with low serum Lp(a) displayed insulin resistance ( P < 0.05), transaminase elevation ( P < 0.05), and increased risk of developing severe fibrosis ( P = 0.007) and cirrhosis ( P = 0.002). In addition, the diagnostic accuracy of Lp(a) in predicting fibrosis increased by combining it with transaminases (area under the curve fibrosis stage 4, 0.87; P < 0.0001). Hepatic LPA expression reflected serum Lp(a) levels ( P = 0.018), and both were reduced with the progression of NAFLD ( P < 0.05). Hepatic LPA messenger RNA levels correlated with those of genes involved in lipoprotein release, lipid synthesis, and fibrogenesis ( P < 0.05). Finally, transmembrane 6 superfamily member 2 ( TM6SF2 ) rs58542926, apolipoprotein E ( ApoE ) rs445925, and proprotein convertase subtilisin/kexin type 9 ( PCSK9 ) rs7552841, known variants that modulate circulating lipids, may influence serum Lp(a) levels ( P < 0.05). Conclusion: Circulating Lp(a) combined with transaminases may represent a novel noninvasive biomarker to predict advanced fibrosis in patients with NAFLD. Abstract : image